2013
DOI: 10.1177/1464884913491652
|View full text |Cite
|
Sign up to set email alerts
|

Local people, local places, local voices and local spaces: How talkback radio in Australia provides hyper-local news through mini-narrative sharing

Abstract: Talkback radio in Australia has primarily been conceptualized as a space where populist meta narratives are constructed and, through repetition, entrenched. However, little attention has been paid to talkback that occurs beyond populist programs. This article focuses on the contributions non-populist talkback programs make to local news and community. It examines commercial and non-commercial talkback programs’ facilitation of the sharing of audiences’ mini-narratives and their provision of hyper-local news. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…In regard to RQ5, audience contributions to the ongoing dialogue, this study found that the lengthy and often heated dialogue not only challenged the journalism presented to them but also introduced new information, opinion, and perspective. In other words, the audience not only reacted with opinion but also reached for meaning, contributing in ways similar to what Ewart (2014) found in a study of talk back radio. For instance, a lengthy dialogue on news-herald.com centered on permission slips for the event, something mentioned by neither the reporting nor those who self-identified as being part of the event.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…In regard to RQ5, audience contributions to the ongoing dialogue, this study found that the lengthy and often heated dialogue not only challenged the journalism presented to them but also introduced new information, opinion, and perspective. In other words, the audience not only reacted with opinion but also reached for meaning, contributing in ways similar to what Ewart (2014) found in a study of talk back radio. For instance, a lengthy dialogue on news-herald.com centered on permission slips for the event, something mentioned by neither the reporting nor those who self-identified as being part of the event.…”
Section: Resultssupporting
confidence: 68%
“…So-called talk back radio, too, has been studied (Berland, 1990; Boggs and Dirmann, 1999). For instance, Ewart (2014) found that some listeners to talk radio in Australia felt ethical imperatives to provide factual information to ongoing discussions on local social issues in ways similar to journalism.…”
Section: Audience Convergencementioning
confidence: 99%
“…Its growing popularity has been theorized as filling a demand for "hyper-local news" that has been abandoned due to media conglomeration (Ewart, 2013). In contrast to nationally syndicated programs such as The Rush Limbaugh Show, it speaks to more concrete local problems, and acts as an electronic town hall for citizens in a regional listening area.…”
Section: Political Talk Radio and Political Mediamentioning
confidence: 99%
“…Hence, metropolitan newspapers are largely conceptualized as city newspapers (cf. Anderson 2013;Ewart 2014;Force 1962;Hanusch 2014). Metropolitan newspapers can therefore be said to be 'local' in orientation.…”
Section: Metropolitanismmentioning
confidence: 99%